"How am I gonna cope?": Caregivers of adolescents with diabetes in Jamaica. (December 2019) - Anderson, M; Tulloch-Reid, MK
Objective: To determine the challenges, coping strategies and needs of urban and rural Jamaican caregivers of adolescents with diabetes, and suggest ways to assist coping. Methods: This qualitative study comprised four focus groups (two urban and two rural) with a total of nineteen caregivers of adolescents with diabetes. Thematic analysis was conducted on the data. Results: The main challenges caregivers faced were keeping their children healthy, managing conflict with their children, and financial concerns. They met these challenges with problem-focused and emotion-focused coping strategies. Caregivers used the problem-focused strategies of vigilance, advocacy, minimising their children's negative emotions, coercion, education, and seeking support, and the emotion-focused strategies of relying on their identity as parents and turning to their faith. Caregivers wanted assistance acquiring medication and equipment, increased diabetes education, and support groups. Discussion: More resources should be channelled toward provision of diabetes supplies. Diabetes education is necessary in schools and for the general public. Healthcare practitioners should explore issues beyond diabetes management, such as caregivers' coping and the caregiver-child relationship. Support groups are needed to facilitate learning. Special attention must be paid to rural areas: rural residents appeared to be in greater need than their urban counterparts.